THE RELATION OF THE BACTERIOSTATIC ACTION OF CERTAIN DYES TO OXIDATION-REDUCTION PROCESSES - René Dubos (1929)
Oxidized indophenols and methylene blue are bacteriostatic for Pneumococcus and hemolytic streptococci of human and bovine origin, while the indigoes, malachite green and litmus are not toxic. 2-Chloroindophenol, the most positive of the indicators of oxidation-reduction potentials used, is also the only one to have a bacteriostatic action on cheese strains of Streptococcus haemolyticus. Methylene blue and the indophenols are no longer bacteriostatic when present in a reduced form in a medium capable of maintaining them in such a condition. A comparison of these results with the growth in plain broth of the organisms studied suggests that the "inhibiting" dyes "poise" the medium at an oxidation potential outside the range in which the inhibited organisms can grow.